Archaeologies of slavery and freedom in the Caribbean : exploring the spaces in between (Florida Museum of Natural History. Ripley P. Bullen series, 2017)
All parts of the Caribbean were shaped by similar forces, including race-based chattel slavery, sugar, capitalism, and the tropical and sometimes deadly natural environment. Within these commonalities, however, is also a great deal of diversity. Large sugar plantations populated by hundreds of enslaved Africans rightfully receive a great deal of attention from archaeologists, historians, and the public. The authors in this volume, however, use innovative techniques and perspectives to reveal the stories of places and times where the rules of this system did not always apply. Collectively, the chapters focus on the spaces in-between, alternate views of plantation landscapes, and the complex dynamics at play in the days following slavery.